Increasing Consumer Purchasing Decisions with Sales Promotion and Service Quality - Humairoh Humairoh; Mohammad Annas (Dinasti International Journal of Economics, Finance & Accounting, 2023)
This study aimed to determine the impact of sales promotion and service quality on purchasing decisions for Emina products in Lazada e-commerce, either partially or simultaneously. The study's approach makes use of a quantitative method. The sample is 96 respondents to Emina users who shop at Lazada e-commerce. The non-probability sampling method was taken by distributing questionnaires to the population in Tangerang City. Records were analyzed using SPSS version 26 software program. The studies resulted in sales promotion having an advantageous and giant impact on purchasing decisions on Emina products in Lazada e-commerce, service quality having a positive and significant effect on purchasing decisions on Emina products in Lazada e-commerce, as well as sales promotion and service quality simultaneously have a positive and significant effect on purchasing decisions on Emina products in Lazada e-commerce, sales promotion has a more have an impact on than service quality on purchasing decisions. Test the studies model of 49.3%.